Personality Characteristics, Anxiety Sensitivity, Anxiety, and Depression Levels on Patients Diagnosed with Psychogenic Pruritus - Kilicaslan, Asli Kazgan; Yildiz, Sevler; Kurt, Osman; Atmaca, Murad (Aves, 2022)
Background: This study aimed to investigate the personality traits, anxiety sensitivity (AS), anxiety, and depression levels in patients diagnosed with psychogenic pruritus (PP). Certain personality traits may come to the fore in psychosomatic disorders; these traits are thought to make the person vulnerable to psychosomatic diseases. This study aimed to investigate the personality traits, anxiety sensitivity (AS), anxiety, and depression levels in patients diagnosed with psychogenic pruritus (PP). Methods: Thirty-seven patients diagnosed with PP (patient group) and 21 healthy controls were included in the study. Sociodemographic Data Form, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Anxiety Sensitivity Index-3 (ASI-3), and Eysenck Personality Questionnaire (EPQ) were administered to all participants. Results: Patients' EPQ scores for the extraversion, neuroticism, psychoticism, and lie subdimensions and EPQ-total scores were significantly higher than those of the control group (P = .001; P < .001; P < .001; P = .008; P < .001, respectively). The total score of ASI-3 scale and the scores of all subdimensions (physical, cognitive, and social) were significantly higher in patients than in controls (P < .001). The BAI (26.8 +/- 9.3) and BDI (24.2 +/- 8.6) total scores of the patients were significantly higher than those of the control group (P < .001). Conclusions: According to EPQ, patients diagnosed with PP are extroverted, but also cold, distrustful, and aloof; show impulsive behavior; are anxious, depressed, and nervous; overly emotional; and prone to lying. Patients suffer more from anxiety, depressive symptoms, and AS in physical, cognitive, and social subdimensions than healthy people. Our findings highlight the importance of psychiatric assessment in PP patients. In this context, we believe that PP deserves to be studied in a broad spectrum with its cognitive, behavioral, and social aspects.
Keywords: Anxiety; anxiety sensitivity; personality; pruritus; psychogenic itch